Mengintegrasikan Tradisi Liturgi Katolik dalam Kurikulum Pendidikan Sekolah - Bagas Setyawan; Diyah Ayu Nur Aisyah; Ravi Choirinur Fajri (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
Catholic liturgy is an important element in the formation of students' faith in Catholic schools. This article discusses how liturgical traditions can be effectively integrated into the educational curriculum. By combining educational theory and theology, this study shows that liturgical practices such as mass, prayer, and meditation not only deepen students' faith but also enhance their sense of community and social responsibility. This article presents concrete examples of the integration of liturgy into spiritual learning and reflection in the classroom.